2017
DOI: 10.1002/2016je005168
|View full text |Cite
|
Sign up to set email alerts
|

The statistical mechanics of solar wind hydroxylation at the Moon, within lunar magnetic anomalies, and at Phobos

Abstract: We present a new formalism to describe the outgassing of hydrogen initially implanted by the solar wind protons into exposed soils on airless bodies. The formalism applies a statistical mechanics approach similar to that applied recently to molecular adsorption onto activated surfaces. The key element enabling this formalism is the recognition that the interatomic potential between the implanted H and regolith‐residing oxides is not of singular value but possess a distribution of trapped energy values at a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 46 publications
7
65
1
Order By: Relevance
“…However, we obtained both a latitudinal and diurnal distributions of hydroxyl more consistent with Li and Milliken (). We attribute this result the ratio of U / T and not solely to local surface temperature (Farrell et al, ). It is not clear what physical processes would lead to uniform hydroxylation at all latitudes.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…However, we obtained both a latitudinal and diurnal distributions of hydroxyl more consistent with Li and Milliken (). We attribute this result the ratio of U / T and not solely to local surface temperature (Farrell et al, ). It is not clear what physical processes would lead to uniform hydroxylation at all latitudes.…”
Section: Discussionmentioning
confidence: 70%
“…The snapshot of the OH concentration after 18 lunations shown in Figure a is consistent with the Li and Milliken () globally averaged map constructed from the M 3 observations, for example, their Figure 1a. Farrell et al () used this same distribution and the preexponential factor to the diffusion coefficient of D 0 = 10 −12 m 2 /s with equation but estimated a dynamic mass fraction that was less than 0.3 ppm at latitudes above 85° for timescales much less than a lunation. Therefore, Farrell et al showed that if 90% of the diffusing H atoms had an activation energy of 0.5 eV and 10% had an activation energy of 0.7 eV, the amount retained would be >30 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations